Unveiling the neural signatures of adolescents with non-suicidal self-injury behavior: an fNIRS study - Liu, Huishan; Li, Gaizhi; Niu, Ying; Li, Qiqi; Zhang, Aixia; Liu, Zhifen (Frontiers in Psychiatry, 2025)
BackgroundNon-suicidal self-injury (NSSI) behavior among adolescents is a significant public health issue, which brings a range of adverse consequences. However, the specific mechanisms underlying this behavior remain unclear. The current study aimed to investigate the hemodynamic activation characteristics of adolescents with NSSI using functional near-infrared spectroscopy (fNIRS) and to explore the correlation of cortical activation with NSSI behavior.MethodsEighteen adolescents with NSSI behavior and 24 healthy controls (HCs) participated in this study. Cortical activation (frontal and temporal lobe hemodynamics) were examined using fNIRS. Self-harm frequency, Self-harm functions, and personality traits were assessed by OSI, NSSI - AT, and EPQ respectively.ResultsThe Δβ value in the dorsolateral prefrontal cortex (DLPFC) area of the NSSI group was significantly higher than that of the HC group, and the activation level of the DLPFC showed a strong positive correlation with the social communication and the expression subscale of the NSSI-AT.ConclusionThe specific manifestation of DLPFC cortical activation in adolescents may serve as a candidate neural correlate for NSSI behavior. Targeted improvement of individual social skills and emotional expression abilities is expected to reduce NSSI behaviors.